Semiotic formations. A metalinguistic and theoretical exploration - Sedda, Franciscu (E|C, 2020)
The semiotic method has formed through a continuous critique and re-discussion of its key conceptsobjects. This has occurred both in search of a unified meta-language and through the production oflocal metalinguistic coherencies. In our paper we would like to move away from the idea of semiotic formations, as found in translation in Lotman’s essay On the Semiosphere, in order to understand its potentialities as a meta-term capable of bringing to a synthesis the sensibility of part of contemporary semiotics. We will show that, while the concept of formations is in a particular relation of complementarity with the idea of text, it is also useful in order to perceive and focus on a set of fundamental semiotic relations – action/passion, process/system, substance/form, polemic/contractual – and therefore to help strengthen a living semiotics.